2011
DOI: 10.1590/s1516-80342011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de transtornos fonológicos em crianças do primeiro ano do ensino fundamental

Abstract: RESUMO INTRODUÇÃOMuitas áreas da Fonoaudiologia carecem de estudos epidemiológicos de alterações para que se possa conhecer não só a incidência e prevalência, mas também o modo de aparecimento dessas alterações nos indivíduos e avançar no entendimento da interferência dessas alterações na qualidade de vida (1) . Em países com maior tradição em estudos epidemiológicos, como os Estados Unidos, a partir do momento em que se identificou a relevância da taxa de prevalência de distúrbios da comunicação, estruturou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The prevalence of oral language disorders indicated by this study is between 21% and 49%, within the same range found in studies carried out in Brazil. 6 , 8 , 16 - 20 This variation is probably due to methodological differences, economic factors and age of the children included in the samples, making it difficult to compare them. The international studies indicate a lower prevalence of alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of oral language disorders indicated by this study is between 21% and 49%, within the same range found in studies carried out in Brazil. 6 , 8 , 16 - 20 This variation is probably due to methodological differences, economic factors and age of the children included in the samples, making it difficult to compare them. The international studies indicate a lower prevalence of alterations.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de alterações de linguagem oral apontada por este trabalho se encontra entre 21% a 49%, mesma faixa encontrada em estudos feitos no Brasil. 6 , 8 , 16 - 20 Essa variação provavelmente se deve a diferenças metodológicas, fatores econômicos e de idade das crianças que compuseram as amostras, o que dificulta a comparação entre eles. Já estudos internacionais apontam menor prevalência de alterações.…”
Section: Discussionunclassified
“…The discriminant validity was defined with the negative predictive value and stands out, pointing out that the instrument well identifies the population that does not have the diagnosis, that is, with typical phonological development. This finding is homogeneous in descriptions of the test properties, both in studies carried out with BP speakers (17,24) and with other languages (21,26) . Furthermore, these studies conclude that there is no significant difference when the age variable applied to picture naming tests is evaluated.…”
Section: Discussionmentioning
confidence: 52%
“…Another study that also has the same population, with the delimitation of cases and analysis circumstances, despite a different methodology (it does not use the ROC curve), evaluated the sensitivity and specificity parameters of the Terdaf instrument (24) . This test was designed to track speech disorders in children and its performance results are lower than those of the IAF, as it is less sensitive and specific, as well as having lower predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…In the vocabulary and phonology subtheme, seven articles 2,6,[13][14][15][16][17] were found and four of them 6,13,15-16 compared the performance of children with typical language development with children with speech and language disorders. The literature reminds the interaction between phonology and vocabulary, early acquisition of these subsystems and the importance of the skills acquired for the later stages of language development 27,28 .…”
mentioning
confidence: 99%